Extreme measures : a thriller - Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2008)
With Rapp away on assignment in Pakistan, CIA Director Irene Kennedy turns to his protégée Mike Nash. Nash has served his government honorably for sixteen years -- first as an officer in the Marine Corps and then as an operative in an elite counterterrorism team run by none other than Mitch Rapp. He has met violence with extreme violence and has never wavered in his fight against the jihads and their culture of death. Nash has fought the war on terrorism in secret without accolades or acknowledgement of his personal sacrifice. He has been forced to lie to virtually every single person he cares about, including his wife and children, but he has soldiered on with the knowledge that his hard work and lethal tactics has saved thousands of lives. But the one thing he never saw coming was that his own government was about to turn on him.